STRATEGI PEMANFAATAN ASET OLEH BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) KUANTAN SINGINGI (Studi Kasus Gedung Universitas Islam Kuantan Singingi) - Agata Niti Fitra; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Kuantan Singingi Islamic University Building is an asset owned by the Kuantan Singingi Regency Government which is currently an idle or unused asset. The purpose of this study is to find out how the asset utilization strategy by the Regional Financial and Asset Management Agency (BPKAD) Kuantan Singingi (case study of the Kuantan Singingi Islamic University Building) and find out what are the inhibiting faktors.. This research uses qualitative research, the data required both primary and secondary are obtained through observation, interviews and documentation. The results showed that based on the analysis of the potentials owned, these assets have a great opportunity to be utilized. However, there are several faktors that hinder its implementation, including: differences in the concept of utilization between the government and the university, the absence of other alternative uses and the absence of other organizations in preparing utilization programs.Keyword: Asset Utilization, Asset Management, Analysis and Asset Utilization Plan, Strategy Asset Utilization.